On the u-th Geometric Conditional Quantile - Yebin Cheng; Jan G. de Gooijer (Tinbergen Institute, 2004)
Motivated by Chaudhuri's work (1996) on unconditional geometric quantiles, we explore the asymptotic properties of sample geometric conditional quantiles, defined through kernel functions, in high dimensional spaces. We establish a Bahadur type linear representation for the geometric conditional quantile estimator and obtain the convergence rate for the corresponding remainder term. From this, asymptotic normality on the estimated geometric conditional quantile is derived. Based on these results we propose confidence ellipsoids for multivariate conditional quantiles. The methodology is illustrated via data analysis and a Monte Carlo study.
Keywords: C14; 330; Asymptotic normality; Bahadur representation; geometric conditional quantile; confidence ellipsoids; kernel function; Nichtparametrisches Verfahren; Theorie